Mari Belajar Mengurus Masa dan Wang (MBMMW) courseware for Tabika KEMAS / Nurul Aqilah Jasni and Wan Safra Diyana Wan Abdul Ghani - Jasni, Nurul Aqilah; Wan Abdul Ghani, Wan Safra Diyana (Universiti Teknologi MARA, Kedah, 2023)
Nowadays, the use of multimedia courseware encompasses all learning stages, especially among children. Money and time are the common topics to be taught to young kindergartners for igniting their basic real-life skills. As an effort to assist teachers in providing good educational materials, Mari Belajar Mengurus Masa dan Wang (MBMMW) courseware is developed based on Tabika KEMAS kindergarten core syllabus for mathematics focusing on money and time management. Proper interactive contents that include various activities and videos are provided in the courseware as the teaching and learning aid for teachers, parents and students. Since there are limitations of current educational materials on money and time in Tabika KEMAS, MBMMW course is developed to assist both teachers and students in providing impactful teaching and learning experience. This could later boost the students’ understanding and learning performance while allowing students to have meaningful activities with teachers and parents. By implementing cognitive theory of multimedia learning (CTML) and user experience (UX) recommendations, MBMMW courseware was carefully developed via ADDIE Model which include phases of analysis, design, development, implementation and evaluation. Functional tests have been conducted to ensure the navigability and functionality of the menu, buttons and links displayed in the courseware. Moreover, user evaluation for MBMMW has also been performed towards understanding the initial acceptance of MBMMW courseware among the users. Results have mostly shown positive reactions from the users, thus acknowledging the usability of MBMMW as an interesting and fun teaching and learning aid for presenting fundamental knowledge about money and time.